Using Questioning During a Directed Reading-Thinking Activity to Improve Comprehension and Reading Attitude of First Grade Students - Hanan, Laura (My University, 2015)
The purpose of this action research study was to determine how questioning during a Directed Reading-Thinking Activity would impact comprehension and reading attitude of first graders. This quasi-experimental pre/posttest design study included 38 students from two first grade classes. Basal reader selections were used. The intervention group used questioning along a continuum while the comparison group used traditional basal reader questions. Two separate independent t tests, using the mean gain scores from the pre/post data and the pre/post Reading Attitudes Survey, failed to establish statistical significance (p=0.06). However a large effect size was documented for comprehension (0.8).
Keywords: Directed reading-thinking activity; Reading attitude; Reading comprehension; Elementary schools; Questioning